Comparison of Logistic Regression and Artificial Neural Network in Low Back Pain Prediction: Second National Health Survey - H Zeraati; M Mahmoudi; K Mohammad; M Parsaeian (Iranian Journal of Public Health, 2012)
Background:The purpose of this investigation was to compare empirically predictive ability of an artificial neural network with a logistic regression in prediction of low back pain.Methods: Data from the second national health survey were considered in this investigation.This data includes the information of low back pain and its associated risk factors among Iranian people aged 15 years and older.Artificial neural network and logistic regression models were developed using a set of 17294 data and they were validated in a test set of 17295 data. Hosmer and Lemeshow recommendation for model selection was used in fitting the logistic regression. A three-layer perceptron with 9 inputs, 3 hidden and 1 output neurons was employed. The efficiency of two models was compared by receiver operating characteristic analysis, root mean square and -2 Loglikelihood criteria.Results:The area under the ROC curve (SE), root mean square and -2Loglikelihood of the logistic regression was 0.752 (0.004),0.3832 and 14769.2,respectively. The area under the ROC curve (SE),root mean square and -2Loglikelihood of the artificial neural network was 0.754 (0.004), 0.3770 and 14757.6,respectively.Conclusions:Based on these three criteria,artificial neural network would give better performance than logistic regression.Although,the difference is statistically significant,it does not seem to be clinically significant.